Environmental, Social, Governance (ESG Score) and Profitability on Stock Return with Audit Quality as Moderation - Chandra, Hendika; Anggriani, Rini; Alpiansah, Restu; Hendri, Wira; Zahrah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research aims to examine the effect of Environmental, Social, and Governance (ESG Score) and Profitability on Stock Return with Audit Quality as moderation in companies listed in the SRI-KEHATI Index for the 2021–2023 period. This research is associative causal with a quantitative approach. The population consists of companies in the SRI-KEHATI Index, and the sample selection is conducted using purposive sampling. Based on the sample criteria, 12 companies met the requirements with a research period of three years, resulting in a total of 36 data samples. In this research a panel data regression model is applied using the Fixed Effect Model (FEM), and the moderation variable is tested using Moderated Regression Analysis (MRA) with EViews 10 software. The results of this research indicate that ESG Score has no effect on Stock Return while Profitability affects Stock Return. Moreover, Audit Quality cannot moderate the effect of ESG Score on Stock Return, and the Audit Quality cannot moderate the effect of Profitability on Stock Return.